2018
DOI: 10.1016/j.jsxm.2018.03.087
|View full text |Cite
|
Sign up to set email alerts
|

Does Endometriosis Affect Sexual Activity and Satisfaction of the Man Partner? A Comparison of Partners From Women Diagnosed With Endometriosis and Controls

Abstract: Background Endometriosis-associated pain and dyspareunia influence female sexuality, but little is known about men's experiences in affected couples. Aim To investigate how men partners experience sexuality in partnership with women with endometriosis. Methods A multi-center case-control study was performed between 2010 and 2015 in Switzerland, Germany, and A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 38 publications
1
23
2
Order By: Relevance
“…We identified 13 studies in women with endometriosis that address the impact of endometriosis on the personal relationships component of the life course. 34,45,62,[70][71][72][73][74][75][76][77][78][79] The category of "personal relationships" is inclusive of social and family connections as well as intimate partner relationships. Endometriosis may interfere with all types of interpersonal relationships, 34,62 but it is sexual health that has garnered the most research interest.…”
Section: Personal Relationshipsmentioning
confidence: 99%
See 1 more Smart Citation
“…We identified 13 studies in women with endometriosis that address the impact of endometriosis on the personal relationships component of the life course. 34,45,62,[70][71][72][73][74][75][76][77][78][79] The category of "personal relationships" is inclusive of social and family connections as well as intimate partner relationships. Endometriosis may interfere with all types of interpersonal relationships, 34,62 but it is sexual health that has garnered the most research interest.…”
Section: Personal Relationshipsmentioning
confidence: 99%
“…Studies have consistently reported impairment in sexual function in women with endometriosis that causes strain on intimate relationships. 45,62,70,72,75,79 In a multicenter Austrian and German study of 125 women with histologically confirmed endometriosis and dyspareunia, most women (78%) reported sexual distress, as measured on the Female Sexual Distress Scale, and 32% reported sexual dysfunction, as measured on the Female Sexual Function Index (FSFI). 74 Only 21% of women reported neither sexual distress nor sexual dysfunction.…”
Section: Personal Relationshipsmentioning
confidence: 99%
“…Endometriosis is an oestrogen-dependent, chronic inflammatory condition, affecting between 5 and 10% of women in their reproductive years [1,2]. The symptoms of endometriosis include dysmenorrhea, dyspareunia, non-menstrual pelvic pain, dyschesia, dys-uria, musculoskeletal pain, fatigue and infertility [37]. Therefore, endometriosis affects women’s quality of life [1,8,9] and often leads to psychological strain [9].…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, there are many studies reporting impaired sexuality in women suffering from endometriosis [ 10 12 ] and subsequent important implications for quality of life in women [ 13 , 14 ]. Regarding the male perspective, there are two quantitative studies comparing sexual functioning of male partners of endometriosis patients to control couples [ 15 , 16 ], with diverging results regarding the increase of sexual dissatisfaction in male partners.…”
Section: Introductionmentioning
confidence: 99%